Palliative care education in undergraduate medical and nursing programs in Colombia: a cross-sectional analysis. - Sánchez-Cárdenas, Miguel Antonio; Tibaquirá, Camila Andrea Navarro; Mantilla-Manosalva, Nidia; Fonseca, David Andrade; Morales, Alexandra Marin; Delgado, Martha Ximena León (BMC Palliative Care, 2024)
Background: The number of people suffering from chronic diseases requiring palliative care (PC) is increasing rapidly. Therefore, PC teaching in undergraduate health science programs is necessary to improve primary PC based on international recommendations and available scientific evidence. Methods: A descriptive cross-sectional study was conducted. Active undergraduate medical and nursing programs that were approved by the Colombian Ministry of Education and integrated PC teaching into their curricula were included in the study. The total sample consisted of 48 programs: 31 nursing and 17 medical programs. Results: PC competencies are distributed throughout the curriculum in 41.67% of programs, in elective courses in 31.25%, and in mandatory courses in 27.08% of the programs. The average PC teaching hours is 81 for nursing and 57.6 for medicine. PC clinical rotations are not offered in 75% of the programs. For undergraduate nursing programs, the most frequent competencies taught are the definition and history of PC and identifying common symptoms associated with advanced disease. In undergraduate medicine, the most common competencies are pharmacological and non-pharmacological pain management and identification of PC needs. Conclusions: PC teaching in undergraduate health science programs mainly addresses the conceptual and theoretical aspects of PC, which are part of the competencies present throughout the programs' curricula. Low availability of PC clinical rotations was identified. Future studies should assess whether the low availability of clinical rotations in PC limits the ability of students to develop the practical competencies necessary to provide quality PC. Trial registration: Not applicable.